2021
DOI: 10.3389/fpsyg.2021.635651
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Psychological Profiles of Elite and Non-elite Athletes

Abstract: One of the main goals of sport psychology is to identify those psychological factors that are relevant for sport performance as well as possibilities of their development. The aim of the study was to determine whether the set of specific psychological characteristics [generalized self-efficacy, time perspective, emotional intelligence (EI), general achievement motivation, and personality dimensions] makes the distinction between athletes based on their (non)-participation in the senior national team, that is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…The study showed that elite athletes with higher results at official competitions were characterized by a higher anaerobic threshold and maximal oxygen uptake. Compared to the group, the athlete was not elite, which is comparable to the literature data [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 87%
“…The study showed that elite athletes with higher results at official competitions were characterized by a higher anaerobic threshold and maximal oxygen uptake. Compared to the group, the athlete was not elite, which is comparable to the literature data [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 87%
“…Based on the participant's feeling, each item was scored as hardly ever (1), sometimes (2), and often (3). The total scores were calculated and interpreted into three levels of anxiety including low (0-10), moderate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and high (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The higher scores indicate the more risk of being anxious during the matches.…”
Section: Measurementsmentioning
confidence: 99%
“…Previous researches have been studied personality characteristics in a variety of sports and found differences among types of sports [15,16], gender [12,17], race [18], skill level and experience [19]. Most studies have been investigated in the highly skilled athletes who were American or lived in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main objectives of sport psychology is to identify those psychological factors that are relevant to sports performance, as well as the possibilities for their development [ 1 ]. Thus, within sport psychology, we find emotional intelligence to be one of the most novel concepts and lines of research of the 21st century, which nowadays is the subject to extensive popularity and research [ 2 , 3 , 4 , 5 ] and understood as the emotional inter or intrapersonal response of an athlete [ 6 ].…”
Section: Introductionmentioning
confidence: 99%